2020
DOI: 10.1021/acsomega.0c02298
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Cadmium Adsorption Capacities of Agricultural Residues and Industrial Fruit Byproducts by the Incorporation of Al2O3 Nanoparticles

Abstract: In this work, two types of residues (industrial fruit byproducts and agricultural wastes) were studies as promising adsorbents for cadmium uptake. Adsorption experiments using the evaluated biomasses (corn crops CC, palm bagasse PB, orange peels OP, and lemon peels LP) were conducted in batch mode by varying initial solution pH (2, 4, and 6) as well as the particle size (0.355, 0.5, and 1 mm). The optimum operating conditions were defined for further adsorption tests. The biomasses were chemically modified wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…The monolayer capacities (Q max ) of P(AA-AN)-talc for the sorption of Pb 2+ , Cd 2+ , Co 2+ , Zn 2+ , and Sr 2+ was compared with other sorbents reported in the literature. As represented in Table 8, the monolayer capacities of P(AA-AN)-talc toward the studied cations are higher than the previously reported values which suggested that P(AA-AN)-talc is a promising sorbent to remove Pb 2+ , Cd 2+ , Co 2+ , Zn 2+ , and Sr 2+ from aqueous solutions (Annadurai et al 2003;Anitha et al 2015;Ghasemi et al 2018;Abou-Lilah et al 2020;Hassan et al 2020;Herrera et al 2020;Abass et al 2021aAbass et al , 2022cKayranli 2021;Alsehli 2021;Abou-Mesalam et al 2022).…”
Section: Comparison Of Monolayer Capacity With Different Sorbents Rep...mentioning
confidence: 57%
“…The monolayer capacities (Q max ) of P(AA-AN)-talc for the sorption of Pb 2+ , Cd 2+ , Co 2+ , Zn 2+ , and Sr 2+ was compared with other sorbents reported in the literature. As represented in Table 8, the monolayer capacities of P(AA-AN)-talc toward the studied cations are higher than the previously reported values which suggested that P(AA-AN)-talc is a promising sorbent to remove Pb 2+ , Cd 2+ , Co 2+ , Zn 2+ , and Sr 2+ from aqueous solutions (Annadurai et al 2003;Anitha et al 2015;Ghasemi et al 2018;Abou-Lilah et al 2020;Hassan et al 2020;Herrera et al 2020;Abass et al 2021aAbass et al , 2022cKayranli 2021;Alsehli 2021;Abou-Mesalam et al 2022).…”
Section: Comparison Of Monolayer Capacity With Different Sorbents Rep...mentioning
confidence: 57%
“…This indicated a binding interaction between Se and the metal ions [16a,17b,20a] . Similarly from the deconvoluted peaks of O1s, for both of Hg(II) and Cd(II), upshifts were observed at the peak of C=O from 531.6 eV to 531.8 eV, the peak of C−O/Se−O from 532.4 eV to 532.6 eV, peak of C−OH from 533.4 eV to 533.8 eV [14d,16a] . At the same time, a small new peak was generated at 530.8 eV which was the characteristic peak of bare metal‐oxide (Figure 5b, 5f).…”
Section: Resultsmentioning
confidence: 76%
“…In particular, in countries with large agricultural production, most of the waste biomasses are not used, only treated by incineration, and a large proportion is also discarded. This universal treatment methods not only causes serious environmental pollution but also waste resources. Therefore, the use of waste biomass to produce value-added products makes our production process more environmentally friendly and can save resources. , Common ways of producing value-added products include extracting pectin, essential oils, and polysaccharides from biomass such as fruit peels with simple methods; , modifying biomass to adsorb wastewater; , and carbonizing/nitrogen-doped biomass; then, it can be used as adsorbents or conductive materials. In addition to the method of modifying biomass, it can also be combined with other functional materials, which is also a promising way to improve performance and develop new materials. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Up to now, biomass materials with large porous structures and high surface area have been widely used in wastewater treatment. In particular, types of biomass or its modifications are employed for wastewater treatment. …”
Section: Introductionmentioning
confidence: 99%